An inhibitor of complement C5 provides structural insights into activation - Reichhardt, M; Johnson, S; Tang, T; Morgan, T; Tebeka, N; Popitsch, N; Deme, J; Jore, M; Lea, S (National Academy of Sciences, 2019)
The complement system is a crucial part of innate immune defenses against invading pathogens. The blood-meal of the tick Rhipicephalus pulchellus lasts for days, and the tick must therefore rely on inhibitors to counter complement activation. We have identified a class of inhibitors from tick saliva, the CirpT family, and generated detailed structural data revealing their mechanism of action. We show direct binding of a CirpT to complement C5 and have determined the structure of the C5-CirpT complex by cryoelectron microscopy. This reveals an interaction with the peripheral macro globulin domain 4 (C5_MG4) of C5. To achieve higher resolution detail, the structure of the C5_MG4-CirpT complex was solved by X-ray crystallography (at 2.7 Å). We thus present the fold of the CirpT protein family, and provide detailed mechanistic insights into its inhibitory function. Analysis of the binding interface reveals a mechanism of C5 inhibition, and provides information to expand our biological understanding of the activation of C5, and thus the terminal complement pathway.